Islam : an overview in comparative perspective - Kamaruzaman, Kamar Oniah (Saba Islamic Media, 2012)
This book gives a comparative perspective to selected themes and concerns in world religions, i.e., the identity crisis of contemporary society and the search for Truth. The fundamental teachings of Islam is presented in contemporary discursive approach. Islamic concepts on relationship and responsibilities are also discussed. The book ends with hope for a promising future.